PENGARUH PEMASARAN HIJAU, CITRA MEREK DAN PENGETAHUAN LINGKUNGAN TERHADAP KEPUTUSAN PEMBELIAN - Yuaniko Paramitra (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The purpose of this study is to analyze the effect of green marketing on green purchase behavior. The research was conducted in an explanatory, and using quantitative. The study sample was 66 of the participants in the environmental care activities. The sampling technique used in this study is purposive sampling. The results showed that the variables of green marketing, brand image and environmental knowledge simultaneously and partially had a positive effect on green purchase behavior. While brand image and environmental knowledge variables can increase the influence of green marketing on purchasing decisions.